Are the adults alright? Reviewing outcomes for adult offspring of parental divorce. Issue 1 (1st February 2021) - Shanholtz, Caroline E.; Irgens, Megan S.; Beck, Connie J.
Abstract: The current paper aims to summarize the psychological literature on offspring who are over the age of 18 at the time of their parents' divorce. The current review identifies the impact of divorce on these families and makes recommendations for the development of theory, methodology, and intervention for working with this population. Adult offspring have a hard time emotionally adjusting to the new family structure, their relationship with their parents suffer, and they are relied on for emotional and financial support by their parents. Additionally, adult offspring question their own ability to negotiate intimate relationships and the value of marriage. It is critical to better understand these families and how we can promote positive family relationships for generations to come.